Implementation Of Zero Waste For Pineapple Farming Groups On Peatlands - Alang, Hasria; Jiu, Cau Kim; Syamsuri, Syamsuri; Mukhtar, Wahdaniah; Ira, Nurmaya Putri; Nuraga, Welly Handa; Rozi, Abdul (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
Pineapples are a key commodity in Sungai Malaya Village. Peat soil is a limiting factor, while partners need fertilizer. However, the high cost and limited availability of fertilizer are problematic. Furthermore, long-term use of chemical fertilizers can further worsen soil conditions. Harvested pineapple waste is often discarded, creating a habitat for various disease vectors. Unsold pineapples are simply piled up until they spoil. Therefore, post-harvest management and agricultural land management on peat soil are essential. The partner in this activity is the Harapan Jaya Farmers Group in Sungai Malaya Village. The purpose of the community service is to educate partners about zero waste and provide training in making pineapple chips and food additives (POC) from pineapple waste. The community service method is Participatory Action Research (PAR), which consists of three stages: preparation, implementation, and evaluation. The results of the community service show that partners have been able to make POC and pineapple chips thanks to a vacuum fryer. Although the initial practice of making chips resulted in poor quality, after several practices, partners were finally able to produce crispy chips that meet standards. The evaluation results also indicate an increase in partners' knowledge and skills. The conclusion of the activity was that POC could be used as a safer alternative fertilizer for partners. Meanwhile, pineapple chips could become a business opportunity for partners in the future